Current Therapies for Human Epidermal Growth Factor Receptor 2-Positive Metastatic Breast Cancer Patients - Larionov, Alexey A. (Frontiers in Oncology, 2018)
The median survival of patients with HER2-positive metastatic breast cancer has more than doubled since the discovery of HER2-targeted treatments: it rose from less than 2 years in 2001 (prior introduction of trastuzumab) to more than 4 years in 2017. The initial generation of HER2-targeted therapies included trastuzumab with taxanes in the 1st line, followed by the addition of lapatinib and by a switch to another cytotoxic agent after progression. Results of CLEOPATRA, EMILIA and TH3RESA trials have changed this clinical practice. The current consensus includes horizontal dual blockade (trastuzumab+pertuzumab) with taxanes or vinorelbine in the 1st line, followed by trastuzumab-emtansine (T-DM1) in the 2nd line, with addition of lapatinib in the later lines of treatment. However, the fast and simultaneous development of new drugs led to a relative shortage of clinical evidence to support this sequence. Triple-positive breast cancers (TPBC), which express both hormonal receptors and HER2, constitute nearly half of HER2-positive cases. For these tumours, the current consensus is to add endocrine therapy after completion of cytotoxic treatment. Again, this consensus is not fully evidence-based. In view of the recent progress in treatment of oestrogen-receptor-positive breast cancers, a series of trials is evaluating addition of CDK4/6 inhibitors, aromatase inhibitors or fulvestrant to HER2-targeted and cytotoxic chemotherapy in TPBC patients. Despite the remarkable progress in treatment of HER2-positive breast cancer, metastatic disease is still incurable in the majority of patients. A wide range of novel therapies are under development to prevent and overcome resistance to current HER2-targeted agents. This review discusses pivotal clinical trials that have shaped current clinical practices, the current consensus recommendations and the new experimental treatments in metastatic HER2-positive breast cancer.